The Effect of Digitalisation of Safety Accountability Program (SAP) on the Improvement of Occupational Safety System - Bremanta Ginting, Ruli; Hamdan, Alifal (Jurnal Sosial Teknologi, 2024)
PT Putra Perkasa Abadi site PT Bukit Asam Tbk is a company engaged in the mining sector with business processes including topsoil removal, overburden removal, haul road maintenance, road construction, pit service, equipment rental, coal getting and coal hauling. The purpose of the study is to analyze the influence of SAP digitalization on the improvement of the occupational safety system, identify the benefits and challenges in the process of digitizing the occupational safety system, and formulate strategies and recommendations to optimize the implementation of the digitalization of the occupational safety system. This research method uses a qualitative approach with data collection methods through literature studies, field observations, in-depth interviews, document analysis, and surveys. One of the steps taken to improve the implementation of the work safety system is the digitalization of the Safety Accountability Program (SAP) of Partners. Based on data obtained through primary data sources from 30 respondents, namely supervisors from 9 Partners of PT Putra Perkasa Abadi site PT Bukit Asam Tbk, and analysis using the Likert scale, it was concluded that SAP digitalization has a great influence on the role of management with an average score of 91, Conditions and workplaces with an average score of 93, awareness and quality of workers with an average score of 91,  project performance with an average score of 92. Research Results: SAP digitalization has been proven to improve the effectiveness of occupational safety systems through increased efficiency, data accuracy, and better decision-making. However, there are several challenges faced, such as resistance to change and system integration. Recommended strategies include improved training, effective communication, and the development of adequate IT infrastructure. This means that, overall, it is very influential in improving the safety system of PT Putra Perkasa Abadi's partner, PT Bukit Asam Tbk with an average score of 92.